Religious Basis of the Muhammadiyah Movement In Indonesia - Refinal; Ismaiza Busti; Desi Asmaret; Dasrizal Dahlan (Solo International Collaboration and Publication of Social Sciences and Humanities, 2025)
Objective: This study aims to analyze the religious foundation of the Muhammadiyah da'wah movement, focusing on the concept of al-ummah and cultural da'wah, as well as the application of the concepts of al-khair, al-ma'ruf, and al-munkar in the practice of da'wah and its impact on the social and economic empowerment of Muslims in Indonesia. Theoretical Framework: The theoretical framework of this research focuses on the concepts of al-ummah, al-khair, al-ma'ruf, and al-munkar in Islamic da'wah, as well as a contextual and progressive approach to cultural da'wah to understand the role of Muhammadiyah in the social and economic development of the people. Literature Review: The literature review discusses the religious foundation of Muhammadiyah which is rooted in the Qur'an and Sunnah, as well as the importance of social empowerment through contextual and cultural da'wah. Although many studies have discussed Muhammadiyah's da'wah, there is still a gap in the application of da'wah to socio-economic empowerment. Methods: This study uses a qualitative approach with case studies and content analysis. The data was collected through in-depth interviews with Muhammadiyah administrators and observation of da'wah practices in several regions, then analyzed thematically. Results: Muhammadiyah da'wah focuses on spiritual aspects as well as socio-economic empowerment through contextual cultural da'wah. However, challenges such as the ideologization of education and the management of pragmatic da'wah still hinder the effectiveness of this movement. Implications: This study emphasizes the importance of developing da'wah more systematically and comprehensively, as well as the integration of education and da'wah to ensure the relevance of Muhammadiyah in social and global dynamics. Novelty: The novelty of this research lies in the analysis of the application of the concepts of al-khair, al-ma'ruf, and al-munkar in Muhammadiyah da'wah which includes spiritual and socio-economic aspects, as well as the identification of challenges in education and pragmatic da'wah management.